Metode Pembelajaran Pendidikan Agama Islam pada Siswa Kelas III SDN 116 Enrekang - Sitti Halipa (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to determine the implementation of Islamic Religious Education learning methods in grade 3 students at SDN 116 Enrekang and supporting factors Islamic religious education learning method in grade 3 students at SDN 116 Enrekang. This type of research is Classroom Action Research (CAR), consisting of two cycles, each cycle consisting of planning, implementation (Pre- Cycle, Cycle I, Cycle II), observation, and reflection. The research methodology in this thesis describes research objects in accordance with the facts found through field research based on the approach used, data sources, research instruments, data collection methods, data processing techniques and analysis of the validity of research data. The results of this study indicate that the implementation of the learning process for Class 3 SDN Enrekang refers to the curriculum design which proceeds from teaching preparation, delivery of subject matter, selection of learning strategy methods. The use of learning methods can add to the repertoire of learning in the field of Islamic religious studies, especially learning at the age of children.